HLA Polymorphism Affects Risk of de novo Mutation of dystrophin Gene and Clinical Severity of Duchenne Muscular Dystrophy in a Southern Chinese Population - Li, Huan; Xiao, Lulu; Wang, Liang; Lin, Jinfu; Luo, Min; Chen, Menglong; He, Ruojie; Zhu, Yuling; Zhang, Cheng (Frontiers in Neurology, 2018)
Immune-mediated pathology has been thought to be an important factor contributing to Duchenne muscular dystrophy (DMD). Allele frequencies of certain HLA types are known to differ between patients with dystrophinopathies and healthy controls with low-resolution HLA gene typing data in limit reports. Using Polymerase chain reactionsequence based typing (PCR-SBT) to genotype 64 children with DMD in HLA-A, -B,-C, -DRB1, and -DQB1 locus and 503 healthy controls in HLA-A, -B, -DRB1 locus,this study aimed to investigate associations of specific HLA alleles with, and their possible roles in the development and clinical phenotypic severity of DMD. The χ2 test was used to evaluate the distribution of allele frequencies in HLA-A, -B, -DRB1 locus between the patients and healthy controls. A significantly higher frequency of HLA-B*07:05 was found in children with DMD compared to that in controls (OR=16.2, 95%CI=2.9–89.3, P<0.046). More importantly,significantly higher frequencies of HLA-A*29:01 (OR=77.308, 95%CI=6.794–879.731, P<0.0160) and HLA-B*07:05 (OR=60.240, 95%CI=9.637–376.535, P<2.41*10-3) was found in patients with de novo mutations (n=14) compared to controls while no difference of HLA alleles frequency ware indicated between patients with inherited mutation and control. The result indicates that HLA alleles is associated with pathogenesis of DMD especially DMD with de novo mutation. We use Vignos scale to estimate the lower limb motor function of patients. The impact of HLA alleles on score of Vignos scale of DMD children was estimated by multiple linear regression. Our study indicates that HLA-A*02:01 may have a dampening effect on the clinical phenotypic severity of DMD, evidenced by the presence of HLA-A*02:01 being associated with lower Vignos score. Our study demonstrates that certain HLA alleles are indeed associated with the pathogenesis and clinical phenotypic severity of DMD.